(untitled) (Journal of Bangladesh Academy of Sciences, 2016)
Investigation of the serum level of copper, zinc, magnesium and manganese in type-2 diabetes mellitus and their possible association with lipid profile was carried out. The comparative study included 100 type-2 diabetic patients in Gr-II and 100 non-diabetic as control in (Gr-I). Results indicated that there is a significant lower level (p < .001) of serum Zn, Cu, Mg and Mn in diabetic patients compared with the control group, showing p value < .001. In type-2 DM patients (Gr-II) there were significant correlations between serum Zn and TAG (r = 0.209) and between Zn and HDL-C level (r = .199) showing p value <.05. Non significant relationships were found in between Zn and lipid profile (TAG, Cholesterol, HDL-C and LDL-C) of control (Gr-I) group. Significant correlation was found between serum magnesium and TAG of control (Gr-I) where p < .01 and non significant correlations were found in serum Mg and total cholesterol, HDL-C, LDL-C of both type-2 diabetic (Gr-II) and control (Gr-I). Significant correlations were also found in between serum of Cu and Mn and TAG of control (Gr-I) where p < .05 and non significant correlations were found in other component of lipid profile of both cases (Gr-II) and control (Gr-I). Journal of Bangladesh Academy of Sciences, Vol. 40, No. 1, 79-85, 2016